The Effect of Canteen Service Quality on Customer Satisfaction among Second-Year Students of Labschool Kebayoran High School - Ahmad Farrel Al Falubi Hidayat (Sean Institute, 2026)
Service quality is an important factor influencing purchase satisfaction in school canteens, as it affects students’ comfort, loyalty, and overall purchasing experience. This study aims to analyze the level of service quality and its influence on customer satisfaction among second-year students at the school canteen. The research employed a quantitative approach using a survey method. Data were collected through a structured questionnaire based on service quality and customer satisfaction indicators, and the responses were analyzed using descriptive statistical techniques. The results show that the majority of students perceive the canteen service positively, particularly in terms of staff friendliness, responsiveness, purchasing efficiency, cleanliness, and price suitability. Most respondents also expressed satisfaction with their purchasing experience, indicated by their willingness to continue buying from the canteen and to recommend it to other students. These findings demonstrate that good service quality contributes significantly to students’ purchase satisfaction. In conclusion, improving and maintaining service quality in school canteens plays an essential role in enhancing student satisfaction and supporting a positive school environment. The results of this study can serve as a reference for canteen managers and schools to improve service practices and optimize student satisfaction.